Performance of the extremophilic enzyme BglA in the hydrolysis of two aroma glucosides in a range of model and real wines and juices. (1st September 2020) - Delgado, Lidia; Parker, Mango; Fisk, Ian; Paradisi, Francesca
Highlights: Use of extremophilic enzymes is a novel approach for aroma enhancement in wines. Halophilic β-glucosidase BglA tolerates high concentrations of glucose, fructose and ethanol. GC–MS shows improved performance of BglA in comparison with commercial preparation in several matrices. BglA is an excellent alternative in early stages of the winemaking process and in the juice industry. Abstract: β-Glycosidases enhance wine aroma by releasing volatile aglycones from non-volatile glycosides. Commercial preparations contain primarily pectinases, with β-glycosidase as a secondary activity, which limits their potential. Here, the extremophilic β-glucosidase A from Halothermothix orenii, ( BglA ) has been compared with Rapidase® for the production of aromatic wines and in the remediation of smoke-tainted wines. Model systems, real juices and wines have been enriched with geranyl glucoside, typical of white varieties, and guaiacyl glucoside, commonly found in red wines exposed to oak and wines made from grapes exposed to smoke. The hydrolytic capacity of BglA was evaluated by measuring the released volatiles in the gas phase with solid-phase microextraction and GC–MS. BglA, despite an apparent instability at low pH, is twice as effective in releasing volatiles in sweeter wines and in grape juices, offering an excellent alternative for the early stages of the winemaking process and in the juice industry.